1988
DOI: 10.1073/pnas.85.4.1199
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell recognition of the circumsporozoite protein of Plasmodium falciparum: immunodominant T-cell domains map to the polymorphic regions of the molecule.

Abstract: The definition of human T-cell antigenic sites is important for subunit vaccine development of a peptide immunogen if the goal is to allow antibody boosting during infection or to stimulate antibody-independent T-ceil immunity. To identify such sites on the circumsporozoite (CS) protein of Plasmodium falciparum, 29 overlapping synthetic peptides spanning the entire CS protein were made and tested for their ability to stimulate peripheral blood lymphocytes from 35 adults living in a P. falciparum malaria-endemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 34 publications
(23 reference statements)
8
153
3
Order By: Relevance
“…This result was not unexpected since it has been frequently reported that peripheral blood T cells from malaria-sensitized individuals have no or low responses to parasite antigens. [29][30][31] This unresponsiveness is most apparent during acute infection. 25,26 However, since all individuals included in our study were parasite free at the time of sample collection, we can exclude that this immunosuppression was due to an acute infection.…”
Section: Resultsmentioning
confidence: 99%
“…This result was not unexpected since it has been frequently reported that peripheral blood T cells from malaria-sensitized individuals have no or low responses to parasite antigens. [29][30][31] This unresponsiveness is most apparent during acute infection. 25,26 However, since all individuals included in our study were parasite free at the time of sample collection, we can exclude that this immunosuppression was due to an acute infection.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in rodents and humans immunized with irradiated sporozoites revealed that not only antibodies, but also CD4 and CD8 cells that exhibited cytotoxic T-cell (CTL) responses or produced cytokines such as interferon-␥ were important components of the protective immune network against the pre-erythrocytic stage of P. falciparum [22]. Target epitopes for these T-cells have been localized to the Cterminal region of the CSP [23][24][25][26]. The recognition that peptide sequences lying outside the CSP repeat were important for induction of humoral and cellular responses against the hepatic stage led to the inclusion of non-repeat portions of the molecule in the next generation of CSP-based vaccines.…”
Section: Wrair-gsk Development Of Rtssmentioning
confidence: 99%
“…46 T-cell reactivity in the P. falciparum pre-erythrocytic antigen, the circumsporozoite (CS) protein is focused on two immunodominant epitope regions at its highly polymorphic carboxyl terminus. 47 No previous study has characterized immunodominance in the MSP1 protein. Such efforts may help in the identification of potential polymorphic regions under selection immune pressures.…”
Section: In Early Ifn-␥ Elispot Assays In 58mentioning
confidence: 99%